Literature for Life: The Context and Conditions of Its Emergence in Thailand, 1940s-50s - Limapichart, Chulalongkorn University, Thailand, Thanapol (Asiatic: IIUM Journal of English Language and Literature, 2011)
This article examines the context and conditions of the emergence of â€œliterature for lifeâ€ (wannakham phuea chiwit) in Thailand. In contrast to previous works that emphasised a single prerequisite such as the role of the Writers' Club, the Communist Party of Thailand, or the importation, translation and circulation of Marxist literature in the country, this article argues that the concept of â€œliterature for lifeâ€ developed out of the dynamic contestations and exchanges among writers, journalists, social critics, and literary scholars of various political and ideological inclinations, namely the conservative, the â€œliberalâ€ and the communist, as each attempted to assert its cultural legitimacy in the period between the end of the Pacific War and the early phase of the Cold War in Thailand.